S. Garfielde (Editor),Compiled Laws of the State of California: Containing All the Acts of the Legislature of a Public and General Nature, Now in Force, Passed at the Sessions of 1850–51–52–53, 663–64 (1853), ch. 125, div. 11, § 127 - (:unkn) unknown (General Publisher, 1850)
Prohibited the carry of a pistol, gun, knife, dirk, bludgeon, or other offensive weapon with intent to assault. Violators punished by fine not to exceed one hundred dollars or imprisonment no more than three months.
--
Keywords: CARRY - INTENT TO COMMIT CRIME